Peningkatan Hasil Belajar IPS Melalui Model Pembelajaran Jigsaw di Kelas VII SMP 5 Kudus - Istiqomatul Mutmainah; Ananda Siska Khoirunnisa; Dany Miftah M. Nur (Journal Pendidikan Ilmu Pengetahuan Sosial, 2024)
When carrying out learning activities, a teacher or educator must pay attention to success in conveying the material correctly. As well as making learning activities more fun, interesting and not boring, for this reason a teacher must be able to use good learning models or methods such as relevant learning according to the material and not just one model that is done repeatedly. To improve better learning outcomes, teachers It is necessary to implement an appropriate learning system or model to attract students to be more active during learning. One of the learning models that can be used in social studies learning is the jigsaw learning model such as at SMP 5 Kudus which uses this learning model in delivering material. The aim of the research is to analyze the results of implementing the jigsaw learning model at SMP 5 Kudus grade VII. This research uses a qualitative approach with interview and observation methods. Data analysis was obtained using interviews, field notes and field practice. Based on the research results, it shows that this jigsaw model of learning is very effective and the results are very good when implemented at SMP 5 Kudus school.